2016
DOI: 10.3109/00952990.2016.1164711
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of marijuana use disorder among adolescents and adults who use marijuana

Abstract: A significant proportion of marijuana users, especially youth, are at risk for having a marijuana use disorder, even at relatively low levels of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 50 publications
0
33
0
2
Order By: Relevance
“…Cannabis users often use alcohol and tobacco (Pacifci et al, 2003; Richter et al, 2016), and association of health outcomes with cannabis use often disappear after controlling for alcohol and tobacco use (Rooke et al, 2013). Thus, the present study takes into consideration these potential confounds in the examination of association between cannabis use reduction and changes in anxiety, depression, sleep quality, and quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…Cannabis users often use alcohol and tobacco (Pacifci et al, 2003; Richter et al, 2016), and association of health outcomes with cannabis use often disappear after controlling for alcohol and tobacco use (Rooke et al, 2013). Thus, the present study takes into consideration these potential confounds in the examination of association between cannabis use reduction and changes in anxiety, depression, sleep quality, and quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, it is clear that both marijuana use and cannabis use disorder (CUD) has increased among young adults since the early 2000s (Caulkins et al, 2015; Grucza et al, 2016; Hasin et al, 2015; Schulenberg et al, 2017). Recent national data indicate that more than half (54%) of U.S. youth have initiated marijuana use by age 21 (Chen et al, 2017), and among past 30-day marijuana users, about one in five young adults (21– 22%) meets diagnostic criteria for CUD (Richter et al, 2016). Further, a study of 1,573 youth aged 12 to 18 attending a primary care appointment in either California or Pennsylvania found prevalence rates of marijuana use that approached those of alcohol use (past year use: 37% vs. 42%, respectively; past year heavy use: 19% vs. 22%, respectively) (D’Amico et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Though estimates vary, several studies have suggested that approximately 8-10% of individuals who have experimented with cannabis at least once in their lifetime develop CUD (Anthony 2006; Lopez-Quintero et al 2011; Wagner and Anthony 2002). Estimates from a more recent, nationally representative survey in the U.S. suggest that the conversion rate to CUD may not be as high for those with lifetime cannabis use (3.5%), but higher among past year users as an estimated 11.6% met criteria for CUD (Richter et al 2017). The rate of conversion from initiation to CUD appears to be higher among adolescents relative to adults.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a study completed in New Zealand, approximately 22% of adolescents who initiated cannabis use by age 16 met criteria for CUD by 21 (Fergusson et al, 2003). In a similar study in the U.S., individuals who began using cannabis before age 15, developed CUD more than twice as often as those who began using cannabis at age 15 or older (Richter et al 2017).…”
Section: Introductionmentioning
confidence: 99%